Organizational culture and participation in local governance: a study on infrastructure projects under LGSP in Bangladesh - Hasan, S.M. Mehedi (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.